Community Empowerment for Tidal Inundation Early Warning System in West Aceh Regency Indonesia - Rita Oktavia; Dian Kristanti; Nursiah Nursiah; Eko Agus Suyono; Wisnu Nurcahyo; Adhy Kurniawan; Baban Muliadi; Nuzullah Nuzullah; Arli Irdawan; Juwita Juwita; Betriza Betriza (Sakura Digital Nusantara, 2026)
Tidal inundation recurs at least twice annually in West Aceh Regency, yet Pasar Aceh Village previously had no Early Warning System (EWS), leaving residents unprepared for recurring flood damage. This community service program, conducted from August to November 2025 with 20 participants, implemented an integrated EWS through four activities: disaster mitigation socialization, EWS training, device installation, and simulation exercises. The program produced an EWS device, a disaster mitigation module, a web-based monitoring system, and a siren alert system. Community competence was evaluated using pre-test and post-test assessments, showing a significant increase in mean scores from 39.7 to 92.0 (a gain of 52.3 points). The installed EWS successfully delivered early warnings prior to flood events, strengthening community coordination and village disaster readiness while improving residents' sense of security in daily activities. These findings confirm that a technology-based community empowerment approach effectively enhances local resilience to tidal inundation, offering a replicable model for similar coastal disaster-prone areas.